DETEKSI KECURANGAN PADA PELAPORAN KEUANGAN - Satria Yudhia Wijaya (Trunojoyo University of Madura, 2016)
This study aims to determine the factors that influence the fraud on the government’s financial statements. The study population was work units of the Ministry of Forestry. The sample selection uses purposive sampling method with a total sample of 691 work units vertical in the period of 2010-2012. The data analysis that used to test the hypothesis is a logistic regression analysis technique. The results show that the variable located far from the center, the unit test quotation by BPK and the ratio of IV quarter expenditure partially have positive and significant effect on the possibility of fraud on the government's financial statements. Meanwhile, the variable of work units that has been tested previously by BPK showed negative and significant effect. The variable unit that located far from the center, the unit is tested quotation BPK previously and the ratio of IV quarter expenditure simultaneously has significant effect on the possibility of fraud on the government's financial statements.